Strategi Public Relation Klinik Pratama Bina Medika Kota Serang Dalam Membangun Brand Awarness - Ades Sulfiah; Dian Utami Amalia; Fahisatul Jannah; Samsiah Nurhasanah; Yeni Febriyanti; Riska Ferdiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research analyzes the public relations communication strategy implemented by Pratama Bina Medika Clinic in building brand awareness as a new health facility. This study uses a qualitative method with a descriptive approach with data collection techniques using interviews and literature studies to determine the effectiveness of direct marketing strategies (direct selling), word of mouth communication (WOM), and digital marketing in introducing health services (clinics) to the public. The research results show that the direct selling strategy through visits to posyandu is effective in building personal relationships with the community, increasing trust, and expanding brand awareness. WOM communication, both directly and via social media, supports the dissemination of wider and more reliable information. The use of digital marketing through social media platforms such as TikTok and Instagram expands the reach of information and facilitates interaction with the public. This holistic approach has succeeded in creating a positive image of the clinic as a provider of quality and affordable health services, while increasing public trust in the services offered.